A Kairos for mental health: Intercultural pastoral theology and transformative action for elderly well-being in Botswana - Madigele, Tshenolo J. (Hervormde teologiese studies, 2025)
Amid contemporary crises of social fragmentation and healthcare inequity, older adults in Botswana endure heightened mental health struggles because of societal isolation, stigma and systemic neglect. This article interrogates how the prophetic urgency and ethical imperatives of the Kairos Document can inform intercultural pastoral theological interventions for elderly mental health. Through a critical literature review, the study analyses cultural perceptions of mental illness and evaluates the role of faith-based initiatives in mitigating stigma and fostering inclusive care networks. Drawing on the Kairos Document’s demand for transformative praxis, the proposed framework integrates pastoral care, traditional healing and biomedical services to address spiritual, cultural and structural dimensions of the crisis. By centring Botswana’s communal values and the Kairos ethos of contextual solidarity, the research advocates for culturally grounded strategies that bridge theological ethics and public health. Contribution: This article emphasises the enduring relevance of the Kairos Document in mobilising faith communities towards justice-oriented responses to contemporary societal ruptures, particularly for marginalised elderly populations.